Wild edible underutilized plants : nutritional, antinutritional, and nutraceutical aspects - Mohan, V. R., 1959-; Tresina, P. S., 1987-; Doss, A., 1979- (Oakville, ON, Canada ; Palm Bay, Florida : Apple Academic Press, 2019)
"Wild Edible Underutilized Plants explores the role of wild plants in human nutrition-a topic that continues to take precedence in various fields of research. Despite the increasing evidence on past and present nutritional roles of wild edible plants, the use of these resources is often overlooked and neglected in countless policy areas. This book emphasizes the importance of these plants and explores their relevance to sustainable agriculture, biodiversity, and public health in different agro-ecological regions. The book implements a conceptual approach to wild plants, focusing on the benefits of incorporating these plants into people's diets and daily lives and the advantage they will provide to future generations. The book also addresses widespread issues of scarcity, proposing solutions that promote food sovereignty and security. Key Features: Highlights the nutritional role of wild edible plants; Discusses potential uses for traditional and indigenous food crops in developing countries; Proposes solutions to food scarcity through the use of wild edible plants"--
OCLC-licensed vendor bibliographic record.
Keywords: Wild plants, Edible; Wild plants, Edible -- Nutrition; HEALTH & FITNESS / Nutrition; SCIENCE / General; SCIENCE / Life Sciences / Botany